(untitled) - Du Toit, Jaco

Cluster graph representations of low-density parity-check codes including non-stationary channel noise estimation (Stellenbosch : Stellenbosch University, 2024)
CITATION: Du Toit, J. 2024. Cluster graph representations of low-density parity-check codes including non-stationary channel noise estimation. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch Univeristy [online]. Available: https://scholar.sun.ac.za/items/6518e04b-66be-4830-967f-205c852787f4